Hepatocellular Carcinoma in South Indian Population: Clinical Profile and AFP Correlation with Radiological Tumor Size - Sahil Ahmad; Shubha Seshadri (Journal of Pharmacy and Bioallied Sciences)
Objectives: To study the clinical profile of hepatocellular carcinoma (HCC) in a tertiary care hospital and alpha fetoprotein correlation (AFP) with radiological tumor size. Materials and Methods: A prospective observational study was conducted from February 2023 to August 2024. There were 57 cases of HCC enrolled. Patient details were noted, such as demographics, clinical characteristics, tumor characteristics, disease severity and their treatment. The data was compiled and analyzed. The outcome measures were association of tumor size with AFP levels. Results: Patients had a mean age of 63.1 years and a BMI of 27.02 kg/m². Common risk factors were diabetes mellitus and alcohol in 47.4% and 43.9%, respectively. The common symptoms were abdominal pain (right hypochondrium) in 40 (70.2%) patients, abdominal distension in 36 (63.2%), jaundice in 19 (33.3%), weight loss in 10 (17.5%), fever in 8 (14.0%). Hepatomegaly was present in 29 (50.9%) patients, ascites in 27 (47.4%), splenomegaly in 10 (17.5%), liver bruit and pleural effusion in 6 (10.5%) patients each, and hepatic encephalopathy in 4 (7.0%) patients. Conclusion: HCC patients were primarily older men with diabetes and alcohol being common risk factors. Abdominal pain and distention remain common findings with complications of cirrhosis, esophageal varices, and pleural effusion. AFP levels and imaging modalities were the most important aids for the diagnosis, management and prognosis. Majority of the treatment remains supportive in the form of transarterial chemoembolization (TACE), transarterial radioembolization (TARE), stereotactic body radiation therapy (SBRT) etc. with few cases demanding interventional therapies.